The relationship between BMI and physical fitness among 7451 college freshmen: a cross-sectional study in Beijing, China - Guo, Tongtong; Shen, Siqin; Yang, Sanjun; Yang, Fan (Frontiers in Physiology, 2024)
Objective: To identify trends in physical fitness test scores of college freshmen and their physical fitness from 2018 to 2021, and to analyze the relationship between college students' Body Mass Index (BMI) and Physical Fitness Index (PFI). Methods: This study obtained physical fitness test data from 7,541 freshmen at a university in Beijing, China, from 2018 to 2021. Analysis of variance (ANOVA) was used to compare the physical fitness indicators among different BMI levels by gender. A nonlinear quadratic regression model was used to evaluate the relationship between BMI and each indicator within gender groups. Results: The BMI of freshmen in China was generally increased over the study period, and BMI levels influenced students' physical fitness indexes to varying degrees. BMI was significantly correlated with the physical fitness indexes and PFI. The increase in BMI had a greater influence on the PFI of males than females. Conclusions: Students with a normal BMI show better physical fitness. A BMI below or above the normal range may result in poor physical fitness. The relationship between BMI and PFI has an inverted u-shaped curve. Physical education programs should be tailored to students with different fitness levels and fundamentals, including but not limited to the development of strength, speed, and other qualities.